Acutely enhancing affective state and social connection following an online dance intervention during the COVID-19 social isolation crisis - Ashlee Humphries; Noor Tasnim; Rachel Rugh; Morgan Patrick; Julia C. Basso (BMC Psychology, 2023)
Abstract The COVID-19 pandemic has forced many throughout the world to isolate themselves from their respective communities to stop the spread of disease. Although this form of distancing can prevent the contraction of a virus, it results in social isolation and physical inactivity. Consequently, our communities have become heavily reliant on digital solutions to foster social connection and increase physical activity when forced to isolate. Dance is a multidimensional form of physical activity that includes sensory, motor, cognitive, rhythmic, creative, and social elements. Long-term, interventional studies in dance have shown positive effects on both mental and social health; however, little has been done to examine the acute effects and no studies to date have explored the relationship between the affective state and social outcomes of dance. We examined the hypothesis that online dance is associated with improvements in affective state and social connection during a time of social isolation, namely, the COVID-19 crisis. Healthy adults (age ≥ 18; n = 47) engaged in a single session of 60 min of self-selected online dance, completing a series of validated self-reported questionnaires before and after class. We found that online dance was associated with improvements in affective state as measured by increased positive affect and self-esteem and decreased negative affect and depressive symptoms. Additionally, online dance was associated with improvements in social and community connectedness. Further, we found that those who experienced the largest increases in self-esteem and decreases in negative affect demonstrated the largest gains in social connectivity. Although in-person dance classes may be optimal for formalized dance training, online dance instruction offers an accessible platform that can provide mental and social health benefits during the COVID-19 social isolation crisis. We conclude that through online dance, individuals can experience a connection between the body, mind, and community.